Effects of Ginger Extract (Zingiber officinale L) on Glycogen Levels Liver on Mice with Hyperglycaemia - Nenny Triastuti; Achmad Basori; Sunarni Zakaria (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
This study aims to prove the effect of ginger extract on rat liver glycogen levels in hyperglycemic. The design of this study is the post-test only control group design with independent variables (free) include a high-fat diet, injections of streptozotocin, the ethanol extract of ginger doses of 300, 400, 500 mg / kg and the dependent variable (dependent) include blood glucose levels ( GTTO II), glycogen levels. Based on this study, the results of different test GTTO end shows significant differences between negative control group and a positive control, a positive control and P1. Besides, also, there is a significant difference between P1 to P2. This suggests that, dosing higher ginger extract can increase the amount of glycogen levels to near normal. Effect of ginger extract on levels of glycogen in the liver of mice were exposed to a high-fat diet and STZ